Social Credit: promising direction of further reforming of the Russian pension system - P. P. Goncharov (Путеводитель предпринимателя, 2020)
Russian pension system faced serious challenges. It’s distributive and insurance components can’t rich aims of pension system in the long-term because of high degree of dependence on demographic situation; it’s accumulative component - because of not enough reliability caused by dependence on conjuncture of the financial market. On our mind, ways of improving the defect of third component can be found. In this connection, scientists face the task to create the conception of investing pension savings, which would provide both increase in stability of pension system and positive influence on other parameters of socioeconomic development of the country.